Characterization of Plasmodium falciparum integral membrane protein Pf25-IMP and identification of its red blood cell binding sequences inhibiting merozoite invasion in vitro (2008)
The identification of proteins present on the surface of Plasmodium falciparum-infected red blood cells as well as of free merozoites has been widely considered as one of the main areas of research in the development of an antimalarial vaccine due to their involvement in the parasite's pathogenesis and invasion mechanisms. Major advances had been accomplished in this area thanks to the analysis of the reported genomic sequence of P. falciparum, allowing for the identification of genes encoding for putative integral membrane proteins. This study reports for the first time the transcription of the MAL8P1.3 gene, which codifies for a 25-kDa integral membrane protein of P. falciparum (FCB-2 strain), namely, Pf25-IMP. Western blot and immunofluorescence assays using goat polyclonal sera indicate that this protein is expressed in erythrocytic asexual blood stages. A highly robust, sensible, and specific receptor-ligand interaction assay allowed identification of two high activity binding peptides (HABPs) derived from Pf25-IMP: 30577 (41YKTANENVKLASSLSDRLSR 60) and 30583 (161LNKKTVVRKIAEGLGYTIVF180). Both HABPs bound with high affinity to human red blood cells (RBCs), and such binding was susceptible to enzyme treatment with trypsin. A common RBC surface receptor of apparently 48 kDa was found for both HABPs, plus an additional 31-kDa receptor for HABP 30577. HABP 30577 inhibited merozoite invasion in vitro by 73%, while HABP 30583 showed a 59% inhibition at 200 ?M concentration. The data suggest a possible role of Pf25-IMP in merozoite invasion to RBCs and support its inclusion in further immunological studies for evaluating its potential as vaccine candidates. Published by Cold Spring Harbor Laboratory Press. Copyright © 2008 The Protein Society.